2017
DOI: 10.1002/cncr.30506
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the survival advantage among patients with prostate cancer who undergo radical prostatectomy or radiotherapy: The limitations of cancer registry data

Abstract: Objective To compare overall survival of patients who underwent radical prostatectomy or radiotherapy versus non-cancer controls in order to discern if there is a survival advantage according to prostate cancer treatment and the impact of selection bias on these results. Patients and Methods A matched cohort study was performed using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database. We identified 34,473 patients age 66 to 75 years without significant comorbidity from who were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The selection of healthy men for curative treatment is also highlighted by the lower 90‐day mortality after RP compared with the background population in a previous Swedish study . Williams and Huo have also demonstrated this selection bias, showing a survival advantage in men receiving both RP and RT vs a PCa‐free comparison cohort. This selection was also reflected in the present study in PCa‐specific mortality (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The selection of healthy men for curative treatment is also highlighted by the lower 90‐day mortality after RP compared with the background population in a previous Swedish study . Williams and Huo have also demonstrated this selection bias, showing a survival advantage in men receiving both RP and RT vs a PCa‐free comparison cohort. This selection was also reflected in the present study in PCa‐specific mortality (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Though propensity score analysis can also reduce the bias associated with unobserved factors, so long as relationships between unobservable and measured factors exist, there is likely to be unmeasured confounding and selection biases that we are not able to control for that may have accounted for a portion of the survival differences observed in our study, as has been reported in other studies using cancer registry data. 38, 39 To further reduce residual confounding by controlling for proxies of unmeasured confounders, high-dimensional propensity score adjustment was also applied. 13 In an attempt to further balance observed and unobserved characteristics between treatment groups over what is possible with propensity score adjustments, we explored the possibility of utilizing instrumental variable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(17, 18) Although these studies have provided a rationale for further studying the impact of local therapy in advanced prostate cancer, the inherent patient and tumor selection bias associated with survivorship outcomes in observational studies limits the ability to make meaningful recommendations based on them. (19, 20) Recent studies have examined the feasibility of RP in men with metastatic hormone sensitive prostate cancer with all showing complication rates comparable to those reported in a series of RP in high-risk localized disease. (2124) Similar results have also been shown in those with castration resistant metastatic disease.…”
Section: Discussionmentioning
confidence: 98%